Entanglement distribution for a practical quantum-dot-based quantum processor architecture - Spiller, T; D'Amico, I; Lovett, B (IOP Publishing, 2007)
We propose a quantum dot (QD) architecture for enabling universal quantum information processing. Quantum registers, consisting of arrays of vertically stacked self-assembled semiconductor QDs, are connected by chains of in-plane self-assembled dots. We propose an entanglement distributor, a device for producing and distributing maximally entangled qubits on demand, communicated through in-plane dot chains. This enables the transmission of entanglement to spatially separated register stacks, providing a resource for the realization of a sizeable quantum processor built from coupled register stacks of practical size. Our entanglement distributor could be integrated into many of the present proposals for self-assembled QD-based quantum computation (QC). Our device exploits the properties of simple, relatively short, spin-chains and does not require microcavities. Utilizing the properties of self-assembled QDs, after distribution the entanglement can be mapped into relatively long-lived spin qubits and purified, providing a flexible, distributed, off-line resource.